eCM 2011
DOI: 10.22203/ecm.v021a08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alginate type and bead diameter on mass transfers and the metabolic activities of encapsulated C3A cells in bioartificial liver applications

Abstract: Liver-assist devices have been developed in the last few decades to support patients with liver failure on the road to recovery or transplantation. Fluidised bed bio-artificial livers -where liver cells are encapsulated within alginate beads -appear to be a valuable alternative to hollow fibre devices for improving mass transfers and enhancing treatment efficacy. This approach nevertheless deserves optimization in terms of bead production. The aim of this study was to investigate the impact of alginate type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 43 publications
(37 reference statements)
2
39
2
1
Order By: Relevance
“…Alginate-based hepatocyte encapsulation is a well-studied subject, based on different materials to enhance bead resistance [18], material biocompatibility [11], [14], hepatocyte viability and functions [36], [37], and cell immunoprotection [38]. According to the different studies presented in the literature, several parameters appeared essential to ensure a successful implantation of cells embedded in a biomaterial:…”
Section: Discussionmentioning
confidence: 99%
“…Alginate-based hepatocyte encapsulation is a well-studied subject, based on different materials to enhance bead resistance [18], material biocompatibility [11], [14], hepatocyte viability and functions [36], [37], and cell immunoprotection [38]. According to the different studies presented in the literature, several parameters appeared essential to ensure a successful implantation of cells embedded in a biomaterial:…”
Section: Discussionmentioning
confidence: 99%
“…Some methods to characterize the porous structure of the 3D networks have been previously reported, such as mercury intrusion porosimetry [3], nitrogen physisorption [4], and the diffusion kinetics of relevant solutes [5]. Nevertheless, these techniques cannot be applied in the presence of cells, nor do they give information about modifications produced at the cell-biomaterial interface due to cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that large microsphere diameters can offer favorable permeability and maintain cell viability by improving the exchange of nutrients and growth factors (4). Furthermore, Gautier et al (53) also demonstrated that microspheres with a large diameter of 1,000 μ m provided a reliable entrapment process for hepatocytes to be used as a bioartificial liver. Accordingly microspheres with a diameter of 800 μ m were employed in our study.…”
Section: Discussionmentioning
confidence: 99%